Modeling of structure of composite material with fiber components - Dykhta, I.; Lobur, M.; Farmaga, I.; Marikutsa, U.; Ciupiński, Ł. (Видавництво Львівської політехніки, 2012)
Main approaches were developed to create the geometric fiber model for further use in research of composite materials.
Keywords: Structure modeling; composite materials; fiber components